Competitive strategies and firm performance: A comparative study of Malaysian and Indonesian small and medium enterprises - Mohd Rosli, M.; Kuswantoro, F.; Che Omar, A.R. (2012)
Increased globalisation process since the conclusion of the Uruguay multilateral trade agreement in 1994 has bought about greater competition in the marketplace and renewed interest in competition theory and empirical work on firm performance. This gives rise to a huge number of theories, frameworks and empirical studies just to describe the relationship between some potential explanatory variables and firm performance. Traditionally, small and medium enterprises (SMEs) confine their activities to the region of their presence, and the fact that most of them remain in their national boundaries. Thus, a majority of the actors in less developed countries give little emphasis on some core competitive strategies in order to survive in such a globalised world. Despite this case, SMEs of different countries may give different emphases on competitive strategies and as a result of this they may perform differently. Due to the hardly found empirical studies of the past, this study compares competitive strategies and performance of Malaysian and Indonesian SMEs. A self administered questionnaire was used to collect data from 386 SMEs in Malaysia and Indonesia. Using an independent-samples t-test, this study found that competitive strategies and firm performance were significantly different between Malaysian and Indonesian SMEs. Mean scores show that the Malaysian SMEs gave more emphasis on firm management and human resource management; whilst the Indonesian SMEs emphasized more on marketing and global orientation. The outward-oriented emphasis of the latter on competitive strategies enabled them to outperform the Malaysian SMEs in nearly all organizational and market performance indicators. The findings in this study prove that firm and human resource managements may be important, but the emphasis on these two competitive strategies is inadequate to enhance performance in the increasingly globalised world.